Analisis Karakteristik dan Kebutuhan Peserta Didik dalam Pembelajaran Bahasa Inggris untuk Pengembangan Modul Ajar - Dewi, Ifti Luthviana (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Analysis of learners' characteristics and needs is important in learning planning, especially in the Kurikulum Merdeka which emphasizes learner-centered learning. This study was conducted with the aim of analyzing the characteristics and needs of students of SMAN 2 Bantul as well as the strategies used by the teaching teacher in learning English. The results of the analysis will later become a reference in the development of teaching modules. The participants of this study were 36 students of class X SMAN 2 Bantul Yogyakarta, who were in the second semester of the 2022/2023 academic year. Instruments in the form of survey questionnaires were distributed to obtain quantitative data. The collected data were then processed and analyzed using quantitative descriptive analysis technique. The results obtained show that the majority of students have a visual learning style in group or paired activities and utilize technology in the process.